Patterns and Predictors of Disciplinary Exclusion Over Time: An Analysis of the SEELS National Data Set. (June 2013) - Bowman-Perrott, Lisa; Benz, Michael R.; Hsu, Hsien-Yuan; Kwok, Oi-Man; Eisterhold, Leigh Ann; Zhang, Dalun
Disciplinary exclusion practices are on the rise nationally, as are concerns about their disproportionate use and lack of effectiveness. This study used data from the Special Education Elementary Longitudinal Study to examine patterns and predictors of disciplinary exclusion over time. Students with emotional/behavioral disorders were most likely to be excluded and be excluded multiple times, followed by students with attention deficit-hyperactivity disorder and students with learning disabilities. For all student groups, being excluded in the first wave was a strong predictor of being excluded at later points in time. Student gender (male students) and ethnicity (African American students) were associated with a greater probability of exclusion over time. Students with higher social skills, as reported by teachers, had a lower probability of being excluded over time. Implications for practice, policy, and future research are discussed.